Detection of campylobacter species: a comparison of culture and polymerase chain reaction based methods - Kulkarni, S P (Copyright 2002 Journal of Clinical Pathology, 2002)
Aims: To investigate the optimal method for the detection of campylobacters from stool samples by comparing selective culture with membrane filtration and the polymerase chain reaction (PCR). Methods: Three hundred and forty three stool samples were investigated by each of the three methods mentioned above. Selective culture was performed with charcoal cefoperazone desoxycholate agar plates. Membrane filtration was performed using cellulose triacetate membranes with 0.45 μm pores placed on blood agar plates. Enteropathogenic campylobacters were detected using a PCR identification algorithm, consisting of screening PCRs and species identification using a PCR enzyme linked immunosorbent assay (PCR-ELISA), both based on the 16S rRNA gene. Results: Of the 343 samples tested, 23 were positive by one or more method. Of these, 17 were positive by selective culture, 12 by membrane filtration, and 20 by the PCR identification algorithm. A total of 18 of 23 positives were identified as C jejuni and/or C coli by the PCR identification algorithm, compared with 14 identified to the genus level by selective culture, and 10 by membrane filtration. Among the remaining five positive samples, one C hyointestinalis was detected only by the PCR identification algorithm; one C upsaliensis was detected only by the PCR identification algorithm; one Campylobacter sp was detected by membrane filtration and selective culture and later identified as C concisus; one Campylobacter sp was detected by membrane filtration alone and later identified as Arcobacter sp; and one Campylobacter sp detected only by selective culture was lost to study and therefore not speciated. There was no significant difference between detection by selective culture and the other two methods. However, detection by PCR was significantly better than by membrane filtration (0.05 > p > 0.02). Conclusion: The PCR identification algorithm can detect and identify Campylobacter spp to the species level and the result is obtained on the same day. However, PCR is expensive, labour intensive, and does not provide an isolate for further identification or typing. Selective culture is as good as the PCR identification algorithm for the detection of the two most common species, C jejuni and C coli, and it is cheap and practical. However, it does miss the less common species, results take 48 hours, and identification is only to the genus level. Membrane filtration showed a low sensitivity compared with the other methods and is not appropriate for the diagnostic laboratory, although it was the only method to detect the Arcobacter sp. The optimum method for the detection of campylobacters from stool samples in the diagnostic laboratory remains selective culture.